Analisis Pencemaran Perairan Pesisir Bedukang, Desa Deniang, Kabupaten Bangka. - Dareen Nadya Rema; Kurniawan Kurniawan; Umroh Umroh (Journal of Tropical Marine Science, 2019)
Administratively Bedukang coastal waters get into the District of Riau Silip Bangka. There is a tin mining activities and farms in the region that directly or indirectly provide significant pressure on water quality in the region. The purpose of this study was to analyze the characteristics of the quality of coastal waters Bedukang and assess the degree of pollution in coastal waters Bedukang using Pollution Index (IP). Methods of data collection was done at 4 stations by purposive sampling. Insitu measurement parameters are parameters of temperature, pH, and salinity and measurement parameters are parameters exsitu TSS, TDS, BOD, Metals Pb and Total Coliform. Analysis of water quality data using Pollution Index (IP). The results show the value of IP, namely at the first station, the station 3 and the station 4, including lightly polluted category with the value of each value of 2.819, 1.025 and 1.022. At station 2 including good water quality category with the pollution index value of 0.919.There are 3 point lightly polluted so it needs special attention from the local government in the utilization of resources in the region.